Analysing the translatability of macular hole size measurements between high-density horizontal and radial OCT scan patterns - Peter Charbel Issa; Leonard Coulibaly; Carmen Baumann; Navid Johannigmann-Malek; Sofia Groselli; Katharina Gabka (BMJ Open Ophthalmology)
Objective To assess the interchangeability of minimum linear diameter (MLD) macular hole (MH) size measurements in high-density horizontal and radial scan modes in optical coherence tomography (OCT).Methods and analysis 60 patients with a MH had repeat high-density OCT volume scans in a horizontal (30 µm interscan-spacing) and a radial (angular 3.75° interscan-spacing) mode, and the MLD was measured by five raters.Results There were no significant differences in the MLD measurements within the horizontal and the radial modes across repeat measurements of each rater in volume scan 1 (all p≥0.14 and p≥0.28, respectively), between volume scans 1 and 2 (all p≥0.14 and p≥0.69), among the raters (p=0.70 and p=0.60), and using all MLD measurements obtained in this study between primary and repeat measurements in volume scan 1 (p=0.10 and p=0.74) and between measurements obtained in volume scan 1 and 2 (p=0.21 and p=0.90).There was a statistically significant difference of −10.05 µm between the mean MLD of all measurements in the horizontal (n=900) and in the radial (n=900) mode (427.91 (±187.01) vs 437.97 (±184.93) µm; p<0.001). However, the variability of these differences around the mean MLD was large (95% limits of agreement −77.31 to 57.21 µm). The mean difference between all horizontal and all radial MLD measurements in a MH was for MHs that had their widest MLD within 15° of the horizontal, vertical and diagonal meridians 0.77 (±13.88) µm, −34.43 (±55.22) µm and −10.39 (± 34.62) µm, respectively.Conclusions Horizontal scans systematically underestimate the maximum MLD if located vertically or diagonally; however, they have less intra-rater and inter-rater and inter-scan variability in MLD measurements as compared with radial scans. Therefore, the two scan modes are not interchangeable but rather complement each other. These results may be limited to the MLD range analysed (125–924 µm).